Vestiges of Transit: Urban Persistence at a Microscale - Brooks, Leah; Lutz, Byron (The Review of Economics and Statistics, 2019)
We document intracity spatial persistence and its causes. Streetcars dominated urban transit in Los Angeles County from the 1890s to the early 1910s, and were off the road entirely by 1963. However, we find that streetcars' influence remains readily visible in the current pattern of urban density and that this influence has not dissipated in the sixty years since the streetcar's removal. We examine land use regulation as both a consequence of streetcars and a mechanism for the persistent effect of streetcars. Our evidence suggests that the streetcar influences modern behavior through the mutually reinforcing pathways of regulation and agglomerative clustering.